The cellular basis of the Southern African forms of rufous & tyrosinase-positive oculocutaneous albinism - Rawoot, Famida (Department of Human Biology, 2016)
Oculocutaneous albinism is a congenital heritable disorder characterised by hypopigmentation of the eyes, hair and skin, together with visual acuity. Ten albinism have been photophobia, nystagmus and decreased different forms of oculocutaneous described. Of these, the tyrosinasepositive and rufous forms are particularly prevalent in Southern Africa. The tyrosinase-positive form manifests as two distinctly different phenotypes with some individuals developing pigmented freckles (ephelides) on their sunexposed regions and others never developing these freckles. To date, studies on the pathophysiology of tyrosinasepositive albinism have been restricted to examination of hairbulbs rather than skin biopsies. The present study utilises light and electron microscopical investigations of both hairbulb and skin melanocytes from the tyrosinasepositive and rufous forms of oculocutaneous albinism to elucidate the cellular aetiology of these disorders. In addition, melanocyte numbers were quantitated in the tyrosinase-positive skin to establish whether the observed hypopigmentation results from a decrease in the size of the melanocyte population. The melanocyte numbers in regions with ephelides were similarly quantiatated in order to see whether these freckles were a consequence of increased melanocyte numbers. The results show, for the first time, that the hypopigmentation observed in tyrosinase-positive albinos is not a consequence of melanocyte paucity and that the regions of ephelides do not contain more melanocytes. Ultrastructural studies show that regions of ephelides and non-ephelides are distinctly different. In regions of ephelides, numerous fully melanised stage IV eumelanosomes, in addition to unmelanised stage I melanosomes, were seen in the melanocyte cytoplasm. Both stage IV and unmelanised stage I melanosomes are transferred to keratinocytes. In ephelis-free regions the melanocyte cytoplasm was filled with numerous unmelanised stage I melanosomes with no evidence of stage IV melanosomes. This suggests that the defect underlying tyrosinase-positive albinism relates to the melanisation process rather than the process of melanosome assembly. In regions of ephelides, the melanocytes are able to produce numerous stage IV melanosomes, and, because these ephelides occur only on sunexposed regions, it is postulated that U.V. exposure induces a "back mutation" resulting in the restoration of the process of melanosome melanisation in these regions of skin. Numerous aberrant melanocyte organelles were also observed in tyrosinase-positive skin. These included dilated RER, distorted mitochondria and bloated Golgi. These ultrastructural observations support the recent report of a candidate gene for tyrosinase-positive albinism, which, it is speculated encodes an integral melanosomal membrane tyrosine transport protein. A defect in tyrosine transport into melanosomes would explain the observed incomplete melanisation of melanosomes in tyrosinase- positive albino skin. In rufous albinism, several aberrant melanosomal shapes were also seen, including "racquet", "crescent"and "comma"shaped melanosomes, all of which were fairly densely melanised. These melanosomes were also about 30% smaller than normal Negroid melanosomes. Upon transfer to keratinocytes, the melanosomes formed membrane-bound "rosette-like" clusters. These findings that the defect in rufous albinism seem to relates suggest to the melanosomal assembly process rather than the melanisation process.